Comparative evidence of two cities on cross-border entrepreneurs and their business success: Auckland and Kuala Lumpur - Nel, Pieter; Abdullah, Moha Asri (Research Publishing Academy, 2019)
Cross-border entrepreneurs in small business are increasingly redefining and reshaping nations. Comparative evidence in the literature of cross border entrepreneurs has been almost non-existent hence filling a significant vacuum in the literature. The purpose of this research is firstly, to compare and contrast the effects of business issues on business success between two cities of Auckland, New Zealand and Kuala Lumpur, Malaysia. This research employs a mixture of both qualitative and quantitative methods. Quantitative data is obtained from primary data that is secured by a survey carried out on immigrant entrepreneurs of small retail business in Auckland and Kuala Lumpur. To enable the study to explore the dimensions with respect to the underlying items, exploratory factor analysis (EFA) and confirmatory factor are conducted using AMOS before a structural model is developed and tested. The research finds that there are factors that positively contribute to the business success of cross-border entrepreneurs in Auckland and Kuala Lumpur. The analysis of the structural paths shows a significant relationship between business issues and business success in both cities. Thus, cross border entrepreneurs can be a great source of employment generation, innovation and future impetus for the economic growth of these respective cities.